Sandwich-Architected Hybrid Organic Crystals with Humidity–Temperature Sensing and Cryogenic Photothermal Actuation - Lan, Linfeng; Wang, Lijie; Wang, Chenguang; Zhang, Hongyu (Nano-Micro Letters, 2026)
The growing demand for personalized health care, smart wearables, and advanced environmental monitoring has spurred the development of multifunctional materials that combine flexibility, environmental adaptability, and diverse functionalities. However, conventional materials often failed to integrate these attributes simultaneously, hindering their applicability in next-generation technologies. Here, we present an organic–inorganic hybrid crystalline material with a unique sandwich-like architecture, in which a flexible organic crystal core is encased by reduced graphene oxide (rGO) and thermoplastic polyurethane (TPU). This strategic integration endows the material with fluorescence, cryogenic flexibility, and electrical conductivity, while also enabling dual sensing and actuation capabilities. The rGO layer facilitates real-time humidity (25–90% RH) and temperature (25–180 °C) sensing through environmental interactions, whereas the differential thermal expansion between TPU and the flexible crystal core drives efficient photothermal actuation at − 150 °C for advanced thermal regulation. The hybrid material exhibits stable performance under extreme conditions, making it a promising candidate for biomedical monitoring, flexible electronics, and energy applications. This work establishes hybrid crystalline materials as versatile and scalable platforms for addressing complex technological demands, paving the way for their application in next-generation multifunctional devices. Highlights: 1 A layered hybrid crystal integrates fluorescence, mechanical flexibility, conductivity, and cryogenic durability via reduced graphene oxide and thermally responsive polyurethane encapsulation. 2 The hybrid crystal enables real-time dual-mode sensing of humidity (1.65% RH−1) and temperature (0.46% °C−1) with high sensitivity and cycling stability. 3 Infrared-induced photothermal actuation at − 150 °C allows reversible crawling and walking under cryogenic conditions. <figure> <picture><source srcset="//media.springernature.com/lw685/springer-static/image/art%3A10.1007%2Fs40820-025-01996-7/MediaObjects/40820_2025_1996_Figa_HTML.png?as=webp" type="image/webp"></picture> </figure>